The Effectiveness of Earthquake and Tsunami Evacuation Symbols and Signs for the Deaf Community in Public Spaces of Banda Aceh - Asrinaldi Asrinaldi; Mustafa Mustafa (Gorga : Jurnal Seni Rupa, 2026)
Banda Aceh, a region prone to earthquakes and tsunamis, necessitates the implementation of clear signs and symbols to facilitate evacuation during emergencies. However, individuals with hearing impairments face challenges in accessing information conveyed solely through spoken or auditory means. This study investigates the efficacy of tsunami evacuation symbols and signs in public areas of Banda Aceh in assisting deaf individuals and compares their performance to international standards. Employing a combination of quantitative and qualitative data collection methods, the study administered questionnaires, conducted in-depth interviews, and facilitated group discussions with deaf residents residing in Banda Aceh. These individuals frequently occupy public spaces such as mosques, shopping centers, and bus terminals. The findings reveal that 85.7% of the surveyed population deemed the evacuation symbols beneficial for disaster preparedness. Nevertheless, only 21.4% expressed satisfaction with the clarity of the symbols’ colors and shapes. Several critical issues were identified, including the symbols’ poor visibility due to inadequate color contrast, size, or damage. Additionally, the signs were not strategically positioned, and insufficient supplementary information, such as maps, visual aids, or sign language translations, was provided. Notably, 78.6% of the respondents emphasized the paramount importance of incorporating sign language into evacuation plans. Consequently, the study concludes that while the symbols in Banda Aceh offer some level of assistance, they lack full accessibility for deaf individuals. The research suggests that signs should adhere to international standards like ISO 7010, enhance readability, and incorporate additional visual tools and sign language to ensure the safety and well-being of all individuals during emergencies.